The Content of Magnetic Material in Black Sand of Yeh Gangga Beach - Rachmawati, Dewi Oktofa; Gunadi, Gede Aris; Risha, Nurfa; Suswandi, Iwan (Universitas Negeri Semarang, 2023)
Yeh Gangga Beach is one of the black sand beaches in the Tabanan district. The abundant black sand on this beach stretches along the shoreline with varying grain sizes. This black sand characterizes the specific surface composition as iron sand deposits with high magnetic mineral content. The very high need and use of magnetic minerals in various fields prompt a study of the magnetic mineral content in the black sand of Yeh Gangga beach.The magnetic material content was determined by the extraction method which was expressed in terms of mass fraction. The grain size distribution was determined by the sieve method using a sieve shaker consisting of six mesh numbers, namely 30, 100, 170, 200, 270, and 325.The density of magnetic materials was determined by the principle of mass and volume ratio. The magnetic susceptibility was tested by using a Bartington MS2B susceptibility meter. Meanwhile, the characterization of the elements and their oxides used non-magnetic methods, namely the X-Ray Fluorescence test.The research results show that the magnetic material fraction of Yeh Gangga black sand reach 84.84% with 58.39% of the grains having sizes in the range 150r ≥90 μm. The magnetic susceptibility value is 28.26 10-6 m3/kg with an Fe element content of 85.15% w. The hematite (Fe2O3) content reaches 81.69%. This magnetic material has a density of 1914.43 kg/m3.